Parental Support for Age-based Indoor Tanning Restrictions - Gilkey, Melissa B. (Am J Prev Med, 2017)
INTRODUCTION: Regulatory agencies, including the U.S. Food and Drug Administration, are considering policies to ban indoor tanning for youth aged <18 years. Using data from a nationally representative sample, this study assessed parental support for age-based bans as well as less restrictive parental permission requirements. METHODS: Data came from an online survey completed by 1,244 parents of adolescents aged 11–17 years. Weighted multivariable logistic regression models assessed correlates of supporting an indoor tanning ban for youth aged <18 years. Data collection and analysis occurred in 2016. RESULTS: Almost two thirds (65%) of parents agreed with indoor tanning bans for youth, with smaller proportions having no opinion (23%) or disagreeing (12%). Support for bans increased with greater perceived harms of indoor tanning for adolescents (OR=2.66, 95% CI=1.97, 3.59) and decreased with greater perceived benefits (OR=0.49, 95% CI=0.36, 0.67). Compared with support for bans, support for parental permission requirements was somewhat higher, with 79% of parents agreeing with the policy. Most parents (60%) agreed with both policies; only 4% disagreed with both. CONCLUSIONS: Age-based indoor tanning restrictions, including bans, engender broad-based support among parents. Communicating the harms of indoor tanning may facilitate the implementation of these policies.